Nested Corrosion - Oz, Zeynep (editor); Tunaboylu, Sevil (Sharjah Art Foundation, 2025)
This book is printed within the scope of the YAZ publication series. YAZ, curated by Zeynep Oz as part of Sharjah Biennial 16, contemplates on the shifts in societal and economic systems we experience in the present day, specifically those in response to the later stages of the accelerated changes in technology and science.
Sharjah Biennial 16, opening in February 2025, is curated Natasha Ginwala, amal Khalaf, Zeynep Oz, AliaSwastika and Megan Tamati-Quennell.
English
Keywords: N4390-5098 Visual Arts. Exhibitions